The Effect of ICT-Based Audio Visual Media on the Recognition of English Vocabulary in Early Childhood - Afaf Azizah; Lilis Madyawati; Febru Puji Astuti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The study aims to determine the effect of audio-visual media based on ICT (Information Communication and Technology) on the introduction of English vocabulary in early childhood in group B students of TK Pertiwi Kapuhan 1 Sawangan District, Magelang Regency. This research was carried out using Pre-Experimental with the type of One Group Pretest-Posttest Design by conducting initial and final measurements. The subjects of this study were students of gruop B TK Pertiwi Kapuhan 1 Sawangan District, Magelang Regency in the 2021/2022 academic year totaling 12 students. The sampling technique in this study used purposive sampling. The data collection method is carried out using the performance method and is measured using a performance assesment sheet based on indicators. The analysis technique used is non-parametric with the Wilcoxon Ranks Test using SPSS IBM version 28.0.1.0 (142). The results showed that ICT (Information Communication and Technology) based audio-visual media had an effect on the introduction of English vocabulary in early childhood. This is evidenced by the results of the Wilcoxon ranks test, a Z value of 3.063 is obtained with a significance level of 0.002 based on the results of the attached SPSS calculation with an average comparison of the initial measurement value of 26.5 and the final measurement of 64.9 after being given treatment using ICT (Information Communication and Technology) based audio-visual media. The results of the study can be said that activities using audio-visual media based on ICT (Information Communication and Technology) affect the introduction of English vocabulary in early childhood.